2017
DOI: 10.1007/s10661-017-5955-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological evaluation of tree species for biomonitoring of air quality and identification of air pollution-tolerant species

Abstract: Identification of tree species that can biologically monitor air pollution and can endure air pollution is very much important for a sustainable green belt development around any polluted place. To ascertain the species, ten tree species were selected on the basis of some previous study from the campus of the University of Burdwan and were studied in the pre-monsoon and post-monsoon seasons. The study has been designed to investigate biochemical and physiological activities of selected tree species as the camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 23 publications
2
18
0
1
Order By: Relevance
“…Leaves and exposed parts of plant act as persistent absorber, which provide large surface area for accumulation and absorption to air pollution (Joshi et al, 2009). The plantation in such polluted industrial areas is site explicit activities of tolerance level of plants to oil and gas pollution (Das & Prasad, 2010;Sen et al, 2017). Research work has been done to check the sensitivity of plant species based on selected parameter i.e., ascorbic acid content, relative water content, chlorophyll content and leaf extract pH but little attention was given to phytoremediation (Rajput & Agrawal 2005;Chauhan & Joshi 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves and exposed parts of plant act as persistent absorber, which provide large surface area for accumulation and absorption to air pollution (Joshi et al, 2009). The plantation in such polluted industrial areas is site explicit activities of tolerance level of plants to oil and gas pollution (Das & Prasad, 2010;Sen et al, 2017). Research work has been done to check the sensitivity of plant species based on selected parameter i.e., ascorbic acid content, relative water content, chlorophyll content and leaf extract pH but little attention was given to phytoremediation (Rajput & Agrawal 2005;Chauhan & Joshi 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the level of apoplastic Asc in Scots Pine needles was strongly correlated with the level of atmospheric O 3 during the seasonal course [34]. Additionally, the premonsoon and postmonsoon seasons, as well as air pollution, were reported to affect the level of AsA in several tree species and led to the identification of air pollution-tolerant tree species [144]. The AsA content increased in the leaves of many herbaceous plants, including crops, growing at polluted sites [145][146][147].…”
Section: Ozonementioning
confidence: 99%
“…Hence, total chlorophyll content of different plants varies from species to species due to photosynthetic process of plants which depends on leaf age, biotic-abiotic conditions and the level of vehicular pollutants (Katiyar and Dubey 2001;Tak and Kakde 2017;Sen et al, 2017). Higher values of chlorophyll content significantly reports that plant has high tolerance to air pollutants.…”
Section: The Chlorophyll Contentmentioning
confidence: 99%
“…Relative Water Content (RWC) is an important factor with in plants which maintains its physiological balance under stressful conditions and enhances the tolerance capacity of the plants to the air pollution (Veni et al 2014;Sen et al 2017). The scrutiny of data in Table 4 revealed that the selected plant species growing alongside the National Highway showed a significant variation in RWC of the leaves.…”
Section: Relative Water Contentmentioning
confidence: 99%